Laser-Induced Nuclear Damage Signaling and Communication in Astrocyte Networks Through Parp-Dependent Calcium Oscillations - Wakida, Nicole M.; Ha, Ryan D.; Kim, Edward K.; Kong, Xiangduo; Yokomori, Kyoko; Berns, Michael W. (Frontiers in Physics, 2021)
Astrocytes are known to respond to various perturbations with oscillations of calcium, including to cellular injury. Less is known about astrocytes’ ability to detect DNA/nuclear damage. This study looks at changes in calcium signaling in response to laser-induced nuclear damage using a NIR Ti:Sapphire laser. Primary astrocytes derived from genetically engineered mice expressing G6Campf genetically encoded calcium indicator were imaged in response to laser induced injury. Combining laser nanosurgery with calcium imaging of primary astrocytes allow for spatial and temporal observation of the astrocyte network in response to nuclear damage. Nuclear damage resulted in a significant increase in calcium peak frequency, in nuclear damaged cells and astrocytes directly attached to it. The increase in oscillation frequency observed in response to damage and the transfer to neighboring cells was not observed in cytoplasm damaged cells. Targeted astrocytes and attached neighboring cells treated with Poly (ADP-ribose) polymerase inhibitor have a significantly lower peak frequency following laser damage to the nucleus. These results indicate the increase in calcium oscillation frequency following nuclear damage is Poly (ADP-ribose) polymerase dependent.